PENINGKATAN HASIL BELAJAR MATEMATIKA STANDAR KOMPETENSI LINGKARAN MELALUI METODE KINESTETIK PADA PESERTA DIDIK KELAS VIII.B SMPN 26 SATU ATAP PALLANTIKANG, KECAMATAN MAROS BARU, KABUPATEN MAROS - Hajar Hajar; Ita Suryaningsih (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This study aims to improve learning outcomes mathematics using kinesthetic method. This type of research is a class action (Classroom Action Research). Subject of the study is overall VIII.B grade students of SMPN 26 One Roof Palantikang. Techniques used in data collection study is observation and tests. The results showed that there was an increase in the study of students with the material circles using kinesthetic methods in SMPN 26 One Roof Pallantikang Maros Baru subdistrict. In the first cycle the average value achieved was 64.17 from the ideal value of 100, which is considered low by percentage of completeness 52.2%, and the second cycle the average value achieved was 78 from the ideal value of 100, which is considered high with completeness percentage of 43.5%. This means an increase learners' learning outcomes which affect the increased ability of learners from lower to higher category category after use kinesthetic learning methods.